The Effectiveness of the Flipped Classroom Learning Model on German Reading Skills - kalambe, Putri diana; Mantasiah, Mantasiah; Yusri, Yusri (Universitas Negeri Makassar, 2025)
Abstract. This study is a Quasi-Experimental research aimed at obtaining data and information regarding the effectiveness of the Flipped Classroom learning model in improving German reading skills at SMAN 3 Makassar. The research population consisted of 175 students from five classes in Grade XII at SMA Negeri 3 Makassar. The sample was selected randomly (random sampling), with Class XII 5 serving as the experimental group, consisting of 34 students, and Class XII 9 serving as the control group, also consisting of 34 students. The mean score of the experimental group during the pre-test was 41.91, which increased to 80.15 in the post-test. The data were analyzed using an independent samples t-test. The analysis results showed that t_calculated (7.380) > t_table (1.996) at a significance level of 0.05. These findings indicate that the Flipped Classroom learning model is effective in improving the German reading skills of students at SMA Negeri 3 MakassarKeyword: Effektivnesss, flipped classroom, Reading, German